Pengaruh Social Media Communication, Lifestyle Terhadap Purchase Intention Dengan Brand Trust Sebagai Variabel Intervening Pada Toko Thriftku.Pngdi Ponorogo - Dea Eka Febrianti; Fery Setiawan; Naning Kristiyana (Jurnal Manajerial, 2025)
Background - Thrift clothing is becoming increasingly popular these days. Young people and teenagers are increasingly following the rapidly evolving fashion world, fueled by the use of social media for marketing. Competition between thrift fashion and social media has become a hot topic in the digital marketing world. Aim - This study aims to understand the level of influence of Social Media Communication and Lifestyle on Purchase Intention with Brand Trust as an Intervening Variable at the Thrifku.png Store. Design / methodology / approach – This research uses a quantitative approach with the aim of finding more accurate results by interpreting numbers. Data were collected using a questionnaire distributed to the study population, namely young people who have seen, are interested in, or purchased thrift fashion products promoted through social media. The sampling method used a Simple Random Sampling technique with 100 respondents. Data were analyzed using the Structural Equation Model (SEM) method and processed using SmartPLS 4. Findings - The results of this study indicate that Social Media Communication does not have a positive and significant influence on purchasing decisions. However, Social Media Communication has a significant influence on Brand Trust. Lifestyle variables have a significant influence on Brand Trust, but do not significantly influence purchasing decisions. Meanwhile, Brand Trust has a significant influence and mediates Social Media Communication and Lifestyle on purchasing decisions. The implementation of this research is for marketing development, especially in terms of Purchasing Decisions for used clothing products (thrift) through social media. Research implication – This research is useful for digital consumer behavior researchers, particularly in specific product segments, specifically thrift products. Furthermore, it can serve as an evaluation tool for thrift businesses in understanding digital consumer behavior. Limitations – The limitation of this research is that it is part of a digital business marketing strategy with social media communication strategy as the main focus of discussion, which is collaborated with Brand theory.